A randomized, double-blinded, placebo-controlled pilot trial of anticoagulation in low-risk traumatic brain injury: The Delayed Versus Early Enoxaparin Prophylaxis I (DEEP I) study - Phelan, Herb A; Wolf, Steven E; Norwood, Scott H; Aldy, Kim; Brakenridge, Scott C; Eastman, Alexander L; Madden, Christopher J; Nakonezny, Paul A; Yang, Lisa; Chason, David P; Arbique, Gary M; Berne, John; et al. (The journal of trauma and acute care surgery, 2012)
Our group has created an algorithm for venous thromboembolism prophylaxis after traumatic brain injury (TBI), which stratifies patients into low, moderate, and high risk for spontaneous injury progression and tailors a prophylaxis regimen to each arm. We present the results of the Delayed Versus Early Enoxaparin Prophylaxis I study, a double-blind, placebo-controlled, randomized pilot trial on the low-risk arm. In this two-institution study, patients presenting within 6 hours of injury with prespecified small TBI patterns and stable scans at 24 hours after injury were randomized to receive enoxaparin 30 mg bid or placebo from 24 to 96 hours after injury in a double-blind fashion. An additional computed tomography scan was obtained on all subjects 24 hours after starting treatment (and therefore 48 hours after injury). The primary end point was the radiographic worsening of TBI; secondary end points were venous thromboembolism occurrence and extracranial hemorrhagic complications. A total of 683 consecutive patients with TBI were screened during the 28 center months. The most common exclusions were for injuries larger than the prespecified criteria (n = 199) and preinjury anticoagulant use (n = 138). Sixty-two patients were randomized to enoxaparin (n = 34) or placebo (n = 28). Subclinical, radiographic TBI progression rates on the scans performed 48 hours after injury and 24 hours after start of treatment were 5.9% (95% confidence interval [CI], 0.7-19.7%) for enoxaparin and 3.6% (95% CI, 0.1-18.3%) for placebo, a treatment effect difference of 2.3% (95% CI, -14.42-16.5%). No clinical TBI progressions occurred. One deep vein thrombosis occurred in the placebo arm. TBI progression rates after starting enoxaparin in small, stable injuries 24 hours after injury are similar to those of placebo and are subclinical. The next Delayed Versus Early Enoxaparin Prophylaxis studies will assess efficacy of this practice in a powered study on the low-risk arm and a pilot trial of safety of a 72-hour time point in the moderate-risk arm. Therapeutic study, level II.